1995
DOI: 10.1143/jjap.34.5462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B-Ions Substitution in [(K1/2Bi1/2)-(Na1/2Bi1/2)](Ti-B)O3 System with B=Zr, Fe1/2Nb1/2, Zn1/3Nb2/3 or Mg1/3Nb2/3

Abstract: Phase relationship in the [(K1/2Bi1/2)1- y (Na1/2Bi1/2) y ](Ti1- x B x )O3 system with B=Zr, Fe1/2Nb1/2, Zn1/3Nb2/3 or Mg1/3Nb2/3 has been investigated by dielectric measurement and X-ray diffractometry. All of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 1 publication
2
16
0
Order By: Relevance
“…This was influenced by the distortion of the crystal lattice because Ti 4+ occupied at the Zr 4+ site. The phase transition for the Zr/Ti ratio (0.6:0.4) found in this study was in agreement with the previous report of Yamada et al [6] who mentioned that the approximate phase transition point of the BNT-BNZ binary system was at a Zr/Ti ratio of 0.6:0.4. Quantitative data of lattice parameters obtained from the comparison between the observed and calculated reflection angles with a selected d-spacing are also given in Table 1.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This was influenced by the distortion of the crystal lattice because Ti 4+ occupied at the Zr 4+ site. The phase transition for the Zr/Ti ratio (0.6:0.4) found in this study was in agreement with the previous report of Yamada et al [6] who mentioned that the approximate phase transition point of the BNT-BNZ binary system was at a Zr/Ti ratio of 0.6:0.4. Quantitative data of lattice parameters obtained from the comparison between the observed and calculated reflection angles with a selected d-spacing are also given in Table 1.…”
Section: Resultssupporting
confidence: 93%
“…For a similar system of BNT-BNZ, Yamada et al [6] predicted only that the phase-transition point of the phase diagram seemed to be approximately at a Zr/Ti ratio of 0.6:0.4. In addition, a study concerning Bi 0.5 Na 0.5 Zr 1-x Ti x O 3 [BNZT] ceramic from a Zr-rich composition has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Our SXRD results bear this out, in agreement with previous work. 15,16 This behaviour is different to the NBT-NBZ solid-solution, where the t < 1 for the whole range and lower symmetry structures (rhombohedral, monoclinic and orthorhombic) are always observed. 14 …”
Section: Synchrotron Xrdmentioning
confidence: 60%
“…Pronin et al [7] found a pseudocubic ferroelectric phase in the interval of 0.18rxr0.4. Yamada et al [8] found that the tetragonal phase boundary extended to approximately x ¼ 0.14. Sasaki et al [9] and Li et al [10] reported that a coexistence of rhombohedral/tetragonal phases lay in the region 0.16rxr0.2 by observing the splitting of XRD peaks near 401 and 471.…”
Section: Introductionmentioning
confidence: 99%